Pengaruh Return on Asset dan NonPerforming Loan Terhadap Capital Adequacy Ratio Pada PT Bank Mega Tbk - Faisal Faisal (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2021)
This study aims to determine the effect of the independent variables on the dependent variable. The independent variable used in this study is Return on Assets, Non Performing Loans. While the dependent variable in this study is the Capital Adequacy Ratio. The data used in this study are quarterly data from 2010 to 2018. The sampling technique used in this study was purposive sampling involving Bank Mega Tbk. The analysis technique used is multiple linear regression analysis. Based on the results of data analysis, this study shows that simultaneously (Simultaneous) Return on Assets, Non Performing Loans have a significant effect on Capital Adequacy Ratio. And individually (partial) Net Interest Margin, Non Performing Loans and Return on Assets have a positive effect on CAR, negatively affect CAR. Determination coefficient results indicate the Adjusted R-squared value of 0.714240 means that the independent variable can explain the dependent variable by 71.42% while the rest is explained by other variables not contained in the model.In this study, the researcher wanted to find out whether there was a significant relationship between Return on Assets, Non-Performing Loans had a significant effect on the Capital Adequacy Ratio. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh antara variabel independen terhadap variabel dependen. Variabel independen yang digunakan dalam penelitian ini adalah Return on Asset, Non Performing Loan. Sedangkan variabel dependen dalam penelitian ini adalah Capital Adequacy Ratio. Data yang digunakan dalam penelitian ini adalah data kuartal selama periode 2010 sampai dengan 2018. Teknik sampling yang digunakan dalam penelitian ini adalah purposive sampling yang melibatkan Bank Mega Tbk. Teknik analisis yang digunakan adalah analisis regresi linear berganda. Berdasarkan hasil analisis data penelitian ini menunjukan secara bersama-sama (Simultan) Return on Asset, Non Performing Loan berpengaruh signifikan terhadap Capital Adequacy Ratio. Dan secara individu (Parsial) Net Interest Margin, Non Performing Loan dan Return on Asset berpengaruh positif terhadap CAR, berpengaruh negatif terhadap CAR. Hasil Koefisien Determinasi menunjukan nilai Adjusted R-squared sebesar 0,714240 artinya bahwa variabel independen dapat menjelaskan variabel dependen sebesar 71,42% sedangkan sisanya dijelaskan oleh variabel lain yang tidak terdapat dalam model.Return on Asset, Non Performing Loan berpengaruh signifikan terhadap Capital Adequacy Ratio KataKunci: Return on Asset, Non Performing Loan, Capital Adequacy Ratio.